2016
DOI: 10.4049/jimmunol.1501293
|View full text |Cite
|
Sign up to set email alerts
|

Human Head and Neck Squamous Cell Carcinoma–Associated Semaphorin 4D Induces Expansion of Myeloid-Derived Suppressor Cells

Abstract: One of the mechanisms by which malignancies can induce immune suppression is through the production of cytokines that affect the maturation and differentiation of inflammatory cells in the tumor microenvironment. Semaphorin 4D (Sema4D) is a proangiogenic cytokine produced by several malignancies, which has been described in the regulation of the immune system. In the present study, we examined the role of human head and neck squamous cell carcinoma (HNSCC)–secreted Sema4D on myeloid cell differentiation. CD33+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 68 publications
0
60
0
Order By: Relevance
“…HNSCCs demonstrate robust accumulation of MDSCs with immune suppressive capacity (9,15,37), but T reg s also contribute to immunosuppression within the HNSCC tumor microenvironment (10,38). Treg function appears to rely upon p110δ signaling(21).…”
Section: Discussionmentioning
confidence: 99%
“…HNSCCs demonstrate robust accumulation of MDSCs with immune suppressive capacity (9,15,37), but T reg s also contribute to immunosuppression within the HNSCC tumor microenvironment (10,38). Treg function appears to rely upon p110δ signaling(21).…”
Section: Discussionmentioning
confidence: 99%
“…Several cellular mediators of immunosuppression within the HNSCC TME have been identified, including myeloid derived suppressor cells (MDSCs) and regulatory T-lymphocytes (Tregs) [ 7 – 10 ]. MDSCs are likely recruited to the TME through chemokine signaling [ 11 , 12 ], expand locally in response to tumor cell secreted semaphorin 4D [ 13 ], and mediate suppression of T-lymphocyte function at least through STAT3-dependent production of arginase [ 14 ]. MDSCs can be divided into granulocytic or monocytic subtypes based on cell surface marker expression [ 15 ], and the relative abundance of each seems to vary amongst tumor types with both phenotypes expanded in patients with HNSCC [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that MDSCs act via arginase I and inducible NO synthase, as well as via indoleamine 2,3-dioxygenase, IL-10, and TGF-β, to suppress T-cell functions [32] . In HNSCC, activation of STAT3 signaling as well as of tumor-derived semaphorin has been described [33,34] . Furthermore, the amount of MDSCs found in cancer patients correlates with poor prognosis and may counteract immune therapeutic approaches using checkpoint inhibitors [35,36] .…”
Section: The Dual Function Of Myeloid Cells In Immunity Against Cancermentioning
confidence: 99%